2012
DOI: 10.4103/0976-0105.105336
|View full text |Cite
|
Sign up to set email alerts
|

Healing efficacy of methanol extract of leaves of Alternanthera brasiliana Kuntze in aged wound model

Abstract: The methanol extract of Alternanthera brasiliana Kuntze (Family: Amaranthaceae) leaf was investigated for its wound healing effect by excision wound model (in vivo) in aged Sprague Dawley rats. In excision wound model, compared to the control group, percent contraction of wound was signi icantly (P < 0.01) higher in A. brasilianatreated group (5% w/w ointment). The collagen, elastin, and hydroxyproline contents of the granulation tissue of A. brasiliana-treated group increased signi icantly (P < 0.01) compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 5 publications
2
35
0
1
Order By: Relevance
“…Increase in stress tolerance capacity of the animals indicates the possible involvement of higher centre (Omeh and Ezeja, 2010). Therefore, the overall result obtained suggested that the aqueous extract of the leaves of Microtrichia perotitii had antinociceptive activity in the hotplate test that may be in part mediated by opoid receptors and therefore can relieve pain which equally justify the use of the plant for toothaches (Barau et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Increase in stress tolerance capacity of the animals indicates the possible involvement of higher centre (Omeh and Ezeja, 2010). Therefore, the overall result obtained suggested that the aqueous extract of the leaves of Microtrichia perotitii had antinociceptive activity in the hotplate test that may be in part mediated by opoid receptors and therefore can relieve pain which equally justify the use of the plant for toothaches (Barau et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A standard wound of uniform 2 cm diameter was formed with the aid of a round seal [21][22][23][24] . The treatment to the excision wounds of the rats was the same as described above.…”
Section: Excision Wound Modelmentioning
confidence: 99%
“…The thin sections were cut and stained with haematoxylin and eosin (Vinothapooshan and Sundar, 2010;Adiga et al, 2010;Barua et al, 2009) and observed under microscope for the histopathological changes such as fibroblast proliferation, collagen formation.…”
Section: Histopathological Examinationsmentioning
confidence: 99%